Comparison of allergic aspermatogenesis with that induced by vasectomy. II. In vitro studies of cell-mediated immunity to sperm after vasectomy in man and guinea-pig. - Muir, V Y (1977)
Transformation of peripheral blood leucocytes was shown to be a valid assay for cell-mediated immunity to sperm in male guinea-pigs immunized with homologous epididymal sperm (ES) in FCA. A heat-treated extract of ES (BES) was used for culture. Possible developement of cell-mediated immunity to sperm after vasectomy was investigated in patients and guinea-pigs, by culture of blood leucocytes before and at intervals after operation. Patients' leucocytes were cultured with a heat-treated extract of human seminal sperm (BHS); guinea-pigs' leucocytes were cultured with BES. These cultures showed no evidence of specific stimulation of leucocytes by sperm extract, up to 1 year after vasectomy in patients, or up to 6 months in guinea-pigs. Similarly, no evidence of delayed hypersensitivity could be demonstrated by skin tests with BES in animals vasectomized 1 year previously. We consider that this study establishes that cell-mediated immunity to sperm does not develop in either man or guinea-pigs, up to 1 year after conventional vasectomy.